MAT gene deregulation and liver cancer - Chirik, Dinesh; S, Arun (Eastern Journal of Medical Sciences, 2024)
Rodent models with low heterogeneity premalignant and malignant lesions provide a valuable contribution to hepatocellular carcinoma (HCC) pathogenesis in the field of research. Studies have been performed in transgenic mice, and rodent strains on signaling pathways deregulation in hepatocarcinogenesis with varying susceptibilities, and human HCC subtypes. Because ethionine, an antagonist of methionine, causes cancer and methyl-deficient diets cause steatohepatitis, followed by the development of HCC, researchers began to look into mechanisms regulating availability of S-adenosylmethionine (SAM) and its role in liver injury, including HCC development. Cirrhotic livers have decreased methionine adenosyltransferase (MATI/III) levels due to oxidation of cysteine residues in the ATP-binding site. MATII upregulation is inhibited by its reaction product, leading to MATI/III downregulation. Decreased MATI/III: MATII activity ratio, along with increased SAM decarboxylation for polyamine synthesis, results in decreased SAM. Some of the molecular pathways associated with specific cancer phenotypes are evolutionarily conserved, according to previous comparative functional genomics research. Cell cycle regulators (WNT/FZD, PI3K/AKT, and MAPK) and key genes (MAPK, IKK/NF-kB) are upregulated in human and rodent HCC progression. Pseudoprognostic markers for HCC include MAT1A/MAT2A switch. Changes in MAT1A expression and SAM levels occur during hepatocarcinogenesis. No evidence of SAM’s therapeutic effect on HCC has been found. The effects of stable MAT1A overexpression or MAT2A/MAT2B inhibition in vivo should be studied first. MAT2A or MAT2B-silenced HepG2 cells proliferate less in leptin. However, intracellular viral vector transduction in vivo has many limitations. This review interprets recent advances in SAM metabolism deregulation in liver injury predisposing to HCC and determining HCC prognosis.